2021
DOI: 10.1002/jcla.23855
|View full text |Cite
|
Sign up to set email alerts
|

Association between aldehyde dehydrogenase 2 gene rs671 G>A polymorphism and alcoholic liver cirrhosis in southern Chinese Hakka population

Abstract: Background Alcoholic liver cirrhosis (ALC) endangering people's health. The association between aldehyde dehydrogenase 2 (ALDH2) gene polymorphisms and ALC is not clear. To analyze the relationship between ALDH2 and ALC among Hakka population in southern China. Methods A total of 292 ALC patients and 278 controls were included in the study. The ALDH2 gene rs671 polymorphism was analyzed by polymerase chain reaction (PCR)‐gene chip. Relevant information and medical records of these participants were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…Zeng et al analyzed the relationship between ALDH2 genotypes, serum liver enzymes, serum lipid levels, serum protein levels and ALC in Hakka population, and logistic regression analysis showed that ALDH2 rs671 A allele increased the risk of developing ALC after adjustment for smoking and alcohol consumption. 50 Our results are consistent with the study. The alcohol intake and ALDH2 enzyme activity of individuals with *1/*2 heterozygotes are in the middle level, which leads to the accumulation of acetaldehyde in the body and makes them more susceptible to alcoholic diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Zeng et al analyzed the relationship between ALDH2 genotypes, serum liver enzymes, serum lipid levels, serum protein levels and ALC in Hakka population, and logistic regression analysis showed that ALDH2 rs671 A allele increased the risk of developing ALC after adjustment for smoking and alcohol consumption. 50 Our results are consistent with the study. The alcohol intake and ALDH2 enzyme activity of individuals with *1/*2 heterozygotes are in the middle level, which leads to the accumulation of acetaldehyde in the body and makes them more susceptible to alcoholic diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Borras et al, also reported no association between AD and ADH1C*1 in European individuals [34]. These reports are contradictory, since the protective effect of Ile350 against risk of AD is consistently reported in different Asian populations [35,36] than in non-Asian populations [19,37]. However, in a Turkish study, rs698 was not associated with AD whereas rs1229984 (Arg47His, also referred to as ADH1B*2) which is in high linkage disequilibrium with rs698 was associated with AD [38].…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have consistently shown the protective effect of ALDH2*2 in east Asians [17][18][19]. Genetic variants of ADH1C and ALDH2 were demonstrated to be significantly associated with AD especially in east Asian population including a meta-analysis [12,[19][20][21].The association between the welldocumented variants rs698 and rs671 is much less explored especially in south Indian population. The aim of the present study is to establish the allele and genotype frequencies of rs698 and rs671 and also to test for association between these two SNPs and AD in the south Indian Tamilian population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important single nucleotide polymorphism (SNP) in the ALDH2 gene is the Glu504Lys polymorphism (SNP rs671, G>A, GAA>AAA), and the ALDH2 rs671 G>A SNP polymorphism has been proven to be a susceptibility site to develop ALC in the southern Chinese Hakka population. 9 The levels of highdensity lipoprotein cholesterol (HDL-C), total cholesterol (TC), and apolipoprotein A-I (apoA-I) were higher among patients with ALC and the G/A genotype in comparison with those with the G/G genotype, while the levels of HDL-C and apoA-I were lower in patients with the G allele in comparison with those with the A allele. Generally, ALDH2 can affect the serum lipid levels through the regulation of oxidative stress in vivo; therefore, gene variation may give rise to dyslipidemia.…”
Section: Pathophysiology and Mechanism Of Lipid Changes In Cirrhosismentioning
confidence: 99%